Hubungan Kerja Antara Pemerintah Desa dengan Badan Permusyawaratan Desa dalam Pelaksanaan Program Pembangunan di Desa Tribur Kecamatan Abad Selatan - Elisabeth Morib; Saryono Yohanes; Hernimus Ratu Udju (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The Village Head and the Village Consultative Body are two parties who are referred to as working partners in the process of implementing development programs in the village, this is because the BPD together with the Village Head determines the Village work program. In addition, the Village Head has the authority to lead the implementation of village government programs, while the BPD institutionally represents the village population and acts as a supervisor for the implementation of government programs in the village. Another function of the BPD is to accommodate and channel the aspirations of the village community. The village head and BPD must have the same thoughts in implementing village government, so that village government can be implemented in accordance with community expectations and demands. The problem formulation in this research is: (1) What is the working relationship between the Village Government and the Village Consultative Body? (2) What are the inhibiting factors in implementing development programs in Tribur village, South Abad District?The results of this research used empirical juridical research methods and the data was analyzed descriptively qualitatively where the focus of the research was planning, implementation, supervision and evaluation; namely research where the data was directly obtained from the research location for 15 people.